Implementation of Tawhid Through Moral Education to Build Santri’s Character in Al Islam Islamic Boarding School Lamongan - Din Muhammad Zakariya (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: This study aimed to understand how tawhid education in Al-Islam Islamic boarding school Tenggulun, and how tawhid implement in moral education to build santri character and how far tawhid and moral relevance in character building and its effect to santri. This study was qualitative, the primary data from this study obtain from literature study, utterances, action, and documentation from institution, directure, head master, teacher staff and santri in Islamic boarding school. The implementation of this study indicated that tawhid education through moral education give strong effect on character building of santri. The effects are tawhid become main basis of education in building character of santri to be moslem who knows their God’s purpose and apply it in every life aspect and ready to preach and fight for Islam; has storng character of tawhid; has understanding of aqidah ahlu sunnah wal jama’ah; has strong spirit to preach; has obvious aqidah wala’ and baro’; has akhlaqul karimah; and apply it to society. Keywords: Implementation, Tawhid, Moral, Character Building, Al-Islam Lamongan